On the determination of optimal time horizon in a control problem in natural resource economics - Ramesh C. Kumar; Fadle M. Naqib (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with issues relating to the determination of optimal time horizon in a typical control problem of optimal extraction of an exhaustible natural resource. The paper extends the recent Highfill-McAsey results to cover all strictly concave utility functions.